Age and Alzheimer’s Disease-Related Oligodendrocyte Changes in Hippocampal Subregions - DeFlitch, Leah; Gonzalez-Fernandez, Estibaliz; Crawley, Ilan; Kang, Shin H. (Frontiers in Cellular Neuroscience, 2022)
Oligodendrocytes (OLs) form myelin sheaths and provide metabolic support to axons in the CNS. Although most OLs develop during early postnatal life, OL generation continues in adulthood, and this late oligodendrogenesis may contribute to neuronal network plasticity in the adult brain. We used genetic tools for OL labeling and fate tracing of OL progenitors (OPCs), thereby determining OL population growth in hippocampal subregions with normal aging. OL numbers increased up to at least one year of age, but the rates and degrees of this OL change differed among hippocampal subregions. In particular, adult oligodendrogenesis was most prominent in the CA3 and CA4 subregions. In Alzheimer’s disease-like conditions, OL loss was also most severe in the CA3 and CA4 of APP/PS1 mice, although the disease did not impair the rate of OPC differentiation into OLs in those regions. Such region-specific, dynamic OL changes were not correlated with those of OPCs or astrocytes, or the regional distribution of Aβ deposits. Our findings suggest subregion-dependent mechanisms for myelin plasticity and disease-reactive OL vulnerability in the adult hippocampus.